1996
DOI: 10.4294/jpe1952.44.281
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Deformation Associated with the 1995 Hyogo-ken Nanbu Earthquake, Japan Derived from GPS Measurements.

Abstract: A large M=7.2 earthquake occurred just below the western part of the Osaka-Kobe megalopolis , southwest Japan on January 17, 1995. The Japanese University Consortium for GPS Research conducted extensive local GPS measurements in and around the hypocentral region to collect near-field data on co-seismic and post-seismic crustal deformation. Adopting old GPS data collected before the earthquake , co-seismic displacement vectors have been obtained at five sites. Horizontal displacements are larger than 0 .4 m in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…This removal of soil may have also caused a local uplift, It should be noted that there is a region of subsidence or small uplift at the northern tip of Awaji Island, though there are only a few benchmarks (028-013 and 028-011). GPS observation by Tabei et al (1996) revealed subsidence of about 2.5 cm at Iwaya, relative to Usuda, central Japan, when comparing the result of February, 1995 with that of November, 1994. Since independent observations with two different techniques detected similar movements around Iwaya, we take this subsidence and small uplift of benchmarks into consideration in the following inversion analysis.…”
Section: Campaign Type Gps Survey Of Control Pointsmentioning
confidence: 99%
“…This removal of soil may have also caused a local uplift, It should be noted that there is a region of subsidence or small uplift at the northern tip of Awaji Island, though there are only a few benchmarks (028-013 and 028-011). GPS observation by Tabei et al (1996) revealed subsidence of about 2.5 cm at Iwaya, relative to Usuda, central Japan, when comparing the result of February, 1995 with that of November, 1994. Since independent observations with two different techniques detected similar movements around Iwaya, we take this subsidence and small uplift of benchmarks into consideration in the following inversion analysis.…”
Section: Campaign Type Gps Survey Of Control Pointsmentioning
confidence: 99%
“…The comparison of horizontal displacements of Hashimoto et al (1996, arrows with open heads in Hashimoto et al (1996) and Tabei et al (1996). Arrows with solid heads and dotted legs indicate those used by Yamagata et al (1996), and they have been translated to arrows with solid legs by minimizing their differences from the open arrows.…”
Section: Geodetic Datasetmentioning
confidence: 99%
“…Tabei et al (1996) derived horizontal and vertical displacements from the results of these surveys by fixing the coordinates of a survey site in Kyoto, and an IGS global tracking site in Usuda. Since both the sites are far from the Kobe-Awaji area, and Hashimoto et al (1996) derived displacements smaller than 1 cm around them, we can expect no serious error due to the assumption of the fixed points.…”
Section: Geodetic Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-seismic displacements derived from these GPS observations close to the earthquake fault are important to constrain the location of the fault. The results are described in Tabei et al (1996) and Kimata et al (1995), and are used to estimate the rupture process (e.g., Yoshida et al, 1996). Figure 3 shows the distribution of 32 GPS sites by name in addition to the active faults.…”
Section: Introductionmentioning
confidence: 99%